Pre-synaptic NO-cGMP pathway modulates vagal control of heart rate in isolated adult guinea pig atria. - Herring, N; Golding, S; Paterson, D (2000)
The role of nitric oxide (NO) in the vagal modulation of heart rate (HR) is controversial. We tested the hypothesis that NO acts via a pre-synaptic, guanylyl cyclase (GC) dependent pathway. The effects of inhibiting NO synthase (NOS) and GC were evaluated in isolated atrial/right vagal nerve preparations from adult (550-750 g) and young (150-250 g) female guinea pigs. Levels of NOS protein were quantified in right atria using Western blotting and densitometry. The non-specific NOS inhibitor N- omega -nitro- L -arginine (L -NA, 100 microM, n=5) significantly reduced the negative chronotropic response to vagal nerve stimulation (VNS) at 3 and 5 Hz in the adult guinea pig. This effect was reversed with 1 m ML -arginine. Similar results were observed with the specific neuronal NOS inhibitor vinyl-N5-(1-imino-3-butenyl)- L -ornithine (L -VNIO, 100 microM, n=7). Inhibition of GC with 1H-(1,2,4)-oxadiazolo-(4, 3-a)-quinoxalin-1-one (ODQ, 10 microM, n=7) also significantly reduced the negative chronotropic response to VNS at 3 and 5 Hz in adult guinea pigs. Neither L -NA (n=6), L -VNIO (n=5) nor ODQ (n=6) changed the HR response to cumulative doses of carbamylcholine in adult guinea pig atria suggesting that the action of NO is pre-synaptic. The HR response to VNS was unaffected by L -NA (n=7) or ODQ (n=7) in young guinea pigs and Western blot analysis showed significantly lower levels of nNOS protein in right atria from young animals. These results suggest a pre-synaptic NO-cGMP pathway modulates cardiac cholinergic transmission, although this may depend on the developmental stage of the guinea pig.